HUBUNGAN HAFALAN AL-QUR’AN TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR - Kholidin, Nor; Yuliantoro, Ahmad Taufiq; Dewi, Tri Ratna; Kencana Dewi, Sri Enggar; Oktalina, Rani (Prodi PGMI STIT Sunan Giri Bima, 2024)
The Quran memorization program is an extracurricular activity that is often considered a flagship program in primary schools because it is believed to provide numerous benefits to students. Several studies have demonstrated that a student's ability to memorize the Quran has a significant correlation with their academic performance. Based on field observations, some students excel in Quran memorization but do not have an advantage in other academic fields. The research objective is to investigate whether there is still a relationship between the level of Quran memorization and students' academic performance. The research method used in this study is quantitative research. The statistics used are nonparametric statistics using the Kendall Tau correlation technique. The research results indicate that: 1) The average memorization of the Qur'an by students is 44 surahs or approximately 1.5 juz. 2) The average academic performance of students is 88. 3) There is a positive correlation of 0.18 between the amount of Qur'an memorization and students' academic performance. The correlation coefficient of 0.18 can be interpreted as a very weak relationship between the variables.